Indirect effects and spatial scaling affect the persistence of multispecies metapopulations. - Bonsall, M; Bull, J; Pickup, N; Hassell, M (2005)
Quantifying the role of space and spatial scale on the population dynamics of ecological assemblages is a contemporary challenge in ecology. Here, we evaluate the role of metapopulation dynamics on the persistence and dynamics of a multispecies predator-prey assemblage where two prey species shared a common natural enemy (apparent competition). By partitioning the effects of increased resource availability from the effects of metapopulation structure on regional population persistence we show that space has a marked impact on the dynamics of apparent competition in multispecies predator-prey assemblages. Further, the role of habitat size and stochasticity are also shown to influence the dynamics and persistence of this multispecies interaction. The broader consequences of these processes are discussed.